Computer Assisted Thermal Complexation Studies of Vanadium with Benzodiazepine Drugs - Sharma, N.; Vashistha, V.K.; Sharma, U.R. (Asian Journal of Chemistry, 2019)
The complexing tendency of vanadium with nifoxipam and lorazepam were carried out by pH metric titration technique in aqueous acid media at different temperatures (298, 308 and 318 K) and an ionic strength of 0.2 M. The degree of complexation was investigated at different pH values. Potentionmetric measurement of hydrogen ion concentration was also studied with the degree of complex formation. The proton-ligand and metal-ligand stability constants were resolved by modified Calvin-Bjerrum pH titration technique (Irving and Rossitti) using computer programming. The important thermodynamic parameters such as Gibb's free energy change (ΔG), entropy change (ΔS) and enthalpy change (ΔH) for the complexation reactions were calculated. The formation of metal complexes was found to be spontaneous, exothermic and conducive in nature at lower temperatures.